Study On The Implementation Of Accreditation Status And Regional Public Service Agencies As A Strategic Model For Improving The Management Of Community Health Centers (Puskesmas) - Alesa, Nelly; Kamaludin, Kamaludin; Suthia Hayu, Rina; Agustina Ekaputri, Retno (International Journal of Science, Technology & Management, 2024)
Indonesia still has public health centre (Puskesmas) health care issues. The data from Bengkulu is comparable to those from the national level. It shows that Puskesmas has not maximised gatekeeping. We need responsible Puskesmas management and high-quality, sustainable health care to address these problems. Puskesmas' accreditation and Regional Public Service Agency status help the government improve Puskesmas administration. We need an improvement strategic model by synchronization because we still implement accreditation and BLUD separately. Given the current situation, this study explores potential synchronization strategies between accreditation and BLUD to enhance Puskesmas management. The study describes the condition of accredited and BLUD Puskesmas, identifies the problems, investigates the role capabilities of the parties involved, seeks to synchronise Puskesmas management, and formulates a strategy to improve management. This qualitative descriptive research uses a case study approach with purposive sampling to examine Puskesmas, an accredited and BLUD school in Bengkulu Province. Researchers conduct in-depth interviews, observations, library studies, and documentation. Researchers analyse data through collection, reduction, presentation, and verification or conclusion. They also triangulate data, sources, and procedures for data validity analysis. This research created a Puskesmas Management Improvement Strategy Model as a Novelty.